The AA2024/CFRP galvanic couple under a dynamic electrolyte drop: modeling and experimental. (10th November 2022) - Vega, J.M.; García-Lecina, E.; Genesca, J.; Montoya, R.
Abstract: Galvanic coupling between AA2024 and Carbon Fiber Reinforced Polymer (CFRP) has been studied under a dynamic electrolyte droplet from both numerical and experimental points of view. 50 μ l droplets of 3.5 wt. % NaCl (initial concentration) were used as electrolyte under 1 atm. of pressure with controlled temperature 24.5( ∘ C ) and relative humidity (83.5 % ). The evaporation of the electrolyte was monitored by Scanning Kelvin Probe during 24h, mimicking atmospheric corrosion phenomena. The electrochemical potential and the high of the droplet was continuously monitored. The finite element approach of the corresponding Nernst-Planck equations in a 2D dynamic domain, with both electrochemical and physicochemical boundary conditions type, provided a good correlation with the experimental findings.